Implementing Bloom’s Revised Taxonomy in Analyzing the Reading Comprehension Questions - Ekalia, Yulian Juita; Selamat, Ely Heldydiana; Jemadi , Fransiskus; Jelimun, Maria Olga; Setiawan, Anjelus A. (Universitas Nusantara PGRI Kediri, 2022)
Bloom's revised taxonomy is the most frequently utilized as an instrument for objective-as a basis for assessment and as a representation for producing objects that evaluate processes ranging from memorization to more complex cognitive levels such as knowledge assessment. It is predicted that the mix of cognitive levels in the 2013 curriculum will drive students to think critically, to think creatively, to be problem solvers, and have a decision maker competencies. Using teaching resources such as textbooks as one of the learning media to train students' critical thinking. The goal of this research is to figure out the cognitive levels in the revised Blooms' Taxonomy utilized in The Ministry of Education and Culture's (MOEC) textbook